2017
DOI: 10.3341/kjo.2017.31.2.165
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Anterior Segment Ocular Parameters in Anisometropia

Abstract: PurposeThe aim of this study was to investigate the differences in anterior segment ocular parameters in anisometropia >1 D.MethodsThis study included 202 eyes of 101 subjects ranging from 10 to 40 years of age with anisometropia of 1 D or more. The subjects were divided into groups according to anisomyopia, anisoastigmatism, and anisohypermetropia. After providing informed consent, each patient underwent a detailed ophthalmological examination including cycloplegic refraction, best-corrected visual acuity, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
5
10
1
Order By: Relevance
“…Among all the aniso-axial length patients, we detected greater tendencies for female patients to develop aniso-axial length and for the right eye to be the longer one, which are consistent with the findings of Linke et al [ 25 ] and Singh et al [ 9 ], respectively. Many studies support the proposition that the dominant eye is the more myopic in patients with myopic anisometropia [ 26 29 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among all the aniso-axial length patients, we detected greater tendencies for female patients to develop aniso-axial length and for the right eye to be the longer one, which are consistent with the findings of Linke et al [ 25 ] and Singh et al [ 9 ], respectively. Many studies support the proposition that the dominant eye is the more myopic in patients with myopic anisometropia [ 26 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…The comparison of binocular parameters in the anisometropic eye was studied previously, indicating that axial length (AL) was the most important factor in anisometropia [ 7 ]. Whether or not other anterior segmental parameters such as corneal power, lens power, and anterior chamber resulting in or related to anisometropia is under debate [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The difference between non-vectorial aniso-TA prevalence and vectorial aniso-TA prevalence was reasonable as the later one took astigmatic axis into consideration Whatever de nition was used, aniso-TA was associated not only with increased interocular differences in CR, but also with AL, possibly due to the relationship among aniso-TA and anisometropia. A similar correlation was reported by Huynh et al [14], O'Donoghue et al [24], Singh et al [29], and Hameshi et al [30]. These studies showed non-vectorial aniso-CA was associated with non-vectorial aniso-TA.…”
Section: Discussionsupporting
confidence: 84%
“…Whatever de nition was used, aniso-TA was associated not only with increased interocular differences in CR, but also with AL, possibly due to the relationship among aniso-TA and anisometropia. A similar correlation was reported by Huynh et al [14], O'Donoghue et al [26], Singh et al [31], and Hameshi et al [32]. These studies showed non-vectorial aniso-CA was associated with non-vectorial aniso-TA.…”
Section: Discussionsupporting
confidence: 84%